The newborn from multiple spontaneous and induced pregnancy - Zuppa, A. A.; De Luca, D.; Scapillati, M. E. (Medicina e Morale, 2001)
The Authors relate about the epidemiologic data of the increased incidence of twinhood occurred in the last decde most of all because of the diffusion of the techniques of pregnancy induction (pharmacologic and by artificial insemination techniques, GIFT and FIVET). The Authors dwell on the clinical apsects of multiple pregnancies, especially for the neonatal sides. In addition, some ethical aspects related to the pregnancy induction are taken into consideration: considerability of the risks in relation to benefits, especially in relation to the increase mortality, and perinatal morbility linked not only to the increased incidence of twinhood, but to the pregnancy induction itself; pregnancy induction intended not as a therapeutic practice, but as a "substitutive" intervention; the advantage of the so called medicine of the desire.